Navigating Ethics and Innovation: The Role of AI in Cultural Heritage - Wibawa, Budi; Rusnalasari, Zulidyana Dwi (Indonesian Scientific Publication, 2024)
The preservation of cultural heritage has become increasingly reliant on Artificial Intelligence and digital technologies, reflecting a global shift toward technology-driven conservation strategies. This narrative review synthesizes evidence from diverse academic sources to examine how AI is being applied to safeguard both tangible and intangible heritage. Literature searches were conducted using Scopus, Web of Science, and Google Scholar, employing keywords such as “Artificial Intelligence,” “cultural heritage preservation,” “digital archiving,” and “machine learning.” Studies were screened based on inclusion criteria emphasizing empirical research, case studies, and reviews published within the last decade. Results reveal four dominant themes: tangible heritage conservation, intangible heritage preservation, environmental monitoring and risk management, and museum and archive engagement. AI has demonstrated strong potential in artifact restoration, predictive maintenance, and revitalization of traditional practices through immersive technologies. However, systemic barriers, including limited financial resources, fragmented governance, and lack of standardized ethical frameworks, hinder its broader adoption. Ethical challenges, particularly concerning cultural representation, data privacy, and inclusivity, further complicate implementation. Innovative solutions such as public-private partnerships, community-driven digitization, and interdisciplinary collaborations present promising pathways forward. The findings highlight both the opportunities and challenges of integrating AI into heritage preservation and emphasize the need for urgent, coordinated strategies to enhance cultural sustainability. This study contributes to the discourse by underscoring the dual imperative of advancing technological adoption while ensuring cultural sensitivity and inclusivity.